Is There an Interest to Use Deuteron Beams to Produce Non-Conventional Radionuclides? - Alliot, Cyrille; Audouin, Nadia; Barbet, Jacques; Bonraisin, Anne-Cecile; Bossé, Valérie; Bourdeau, Cécile; Bourgeois, Mickael; Duchemin, Charlotte; Guertin, Arnaud; Haddad, Ferid; Huclier-Markai, Sandrine; Kerdjoudj, Rabah; et al. (Frontiers in Medicine, 2015)
With the recent interest on the theranostic approach, there has been a renewed interest for alternative radionuclides in nuclear medicine. They can be produced using common production routes i.e. using protons accelerated by biomedical cyclotrons or neutrons produced in research reactors. However, in some cases, it can be more valuable to use deuterons as projectiles. In the case of Cu-64, smaller quantities of the expensive target material, Ni-64, are used with deuterons as compared with protons for the same produced activity. For the Sc-44m/Sc-44g generator, deuterons afford a higher Sc-44m production yield than with protons. Finally, in the case of Re-186g, deuterons lead to a production yield five times higher than protons. These three examples show that it is of interest to consider not only protons or neutrons but also deuterons to produce alternative radionuclides.